O sedevacantismo segundo Michel-Louis Guérard des Lauriers, O. P. - Coelho, Renato Arnellas (2015)
After the Second Vatican Council (1962-1965), some people start to follow positions known as sedevacantists, denying the existence of a pope in the Church after that period. Sedevacantism is more present in the United States and in Europe, but also, gradually, some people in Brazil adhere to this position. Among the many branches of sedevacantism, the Cassiciacum Thesis is noteworthy, formulated by the Dominican Michel Guérard des Lauriers (1898-1988). This paper will examine the importance of the life and work of the author of the Cassiciacum Thesis, in order to understand what sedevacantism is, as well as compare this Thesis with favorable and unfavorable scholars. One will see that this Thesis approaches the subject of papacy in a creative way, unlike other approaches done so far. Nevertheless, one can conclude that the Thesis is limited both intrinsically, due to its arguments, and extrinsically, by relying on a subjective analysis restricted to a particular and fleeting papacy